PENGARUH PEMBERDAYAAN, EFIKASI DIRI DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SMKN 1 BALIKPAPAN - jurnalpps pps; Asfianty Abbas Hasan Yumus (Prodi Magister Manajemen Universitas Wijaya Putra, 2022)
This study aims to examine the effect of empowerment, self-efficacy and organizational culture on the teaching performance of teachers at SMK Negeri I Balikpapan, East Kalimantan Province, both separately and simultaneously. The research population was all teachers of SMK Negeri I Balikpapan, totaling 127 teachers and a sample of 82 people through purposive sampling technique. The research design is classified as ex-post-facto, with descriptive causal correlational research explanatory methods. Collecting data using a questionnaire instrument and study documentation. The results showed that there was a positive and significant effect of empowerment, self-efficacy, and organizational culture on the teaching performance of teachers at SMK Negeri I Balikpapan, East Kalimantan Province with the results of the study: Teacher Empowerment, Self-Efficacy, and Organizational Culture at SMKN I Balikpapan, East Kalimantan in good category , there is a simultaneous influence between teacher empowerment, self-efficacy, and organizational culture on teacher performance at SMK Negeri I Balikpapan, East Kalimantan, and there is a partial influence between teacher empowerment, selfefficacy, and organizational culture on teacher performance at SMK Negeri I Balikpapan Kalimantan East.